Knowledge of preservice elementary teachers on fractions - Castro-Rodríguez, Elena (2021)
In this paper, we studied the knowledge on didactic contents reflected by future elementary teachers when answering questions related to teaching and learning fractions. Following a qualitative methodology, specifically a case study, 9 senior pre-service elementary teachers were interviewed using a structured approach. The topic was presented to the subjects using a narrative they had previously written on how to initiate the concept of fractions with school children. After reading it, they were asked questions regarding task design, learning objectives, and mistakes and difficulties. Results identified two trends in the participants’ knowledge: a procedural or technical trend in which the stated knowledge emphasizes procedures, processes, or action modes, and a conceptual or cognitive trend in which the stated knowledge emphasizes the functional understanding of fractions and their relationships. As a conclusion, it is essential that initial teacher training emphasizes mathematical as well as didactic contents.